Neuropsychiatric complications of efavirenz in children with HIV-1 infection - Hammond Charles (Division of Neurology, 2019)
Background: Efavirenz is associated with transient neuropsychiatric manifestations but the impact on neurocognition is unknown. Genetically determined black South Africans who are slow metabolizers of efavirenz may be at risk of toxicity. This study describes neuropsychiatric and neurocognitive manifestations of South African children with suspected efavirenz neurotoxicity. Method: This retrospective study describes clinical features of 12 children with suspected efavirenz neurotoxicity (2008 – 2014). Results: Twelve children were referred (aged 3 years 4 months to 12 years, mean 7 years 8 months; 8 indigenous African (black) and 4 mixed ancestry). Six had acute neuropsychiatric manifestations after 2-8 weeks (mean 5 weeks) on efavirenz including drowsiness, seizures, sleep disturbances, behavioural changes, ataxia and slurred speech. Symptoms resolved over a few weeks in four. Two black children were phenotypically slow metabolizers with high plasma efavirenz concentrations above normal range resulting in discontinuation of efavirenz. Nine children had neurocognitive concerns potentially exacerbated by long-term efavirenz (6-72 months therapy; mean 31 months), and showed poor performance in all neurocognitive domains. Conclusion: Efavirenz causes transient neuropsychiatric adverse effects and may contribute to poor longterm neurocognitive outcomes in HIV-infected children. Genetically slow metabolizers are at risk of neurotoxicity. Prospective studies comparing efavirenz-treated and efavirenz-naïve children are needed.